2019
DOI: 10.3390/agronomy9040206
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variation in Diurnal Photosynthesis and Chlorophyll Fluorescence of Four Genotypes of Cassava (Manihot esculenta Crantz) under Irrigation Conditions in a Tropical Savanna Climate

Abstract: Photosynthesis performance during early vegetative growth is an important physiological trait determining yield of cassava, but limited information is currently available for the tropical savanna climate of Asia. Diurnal photosynthesis and chlorophyll fluorescence of the three-month-old plants of four commercial cassava genotypes (Rayong 9, RY9; Rayong 11, RY11; Kasetsart 50, KU50 and CMR38-125-77) grown under irrigation, were investigated in three seasons i.e., rainy, cool and hot. The mean daily net photosyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 60 publications
3
13
0
Order By: Relevance
“…Satisfactory performances for CMR38-125-77 on chlorophyll fluorescence, storage root dry weight, growth rate, total dry weight, starch content and starch yield have been reported in the previous investigations conducted in different upper paddy fields in rotation with rice (off-season) [12,13,35], as well as experiments conducted in different growing seasons under full irrigation in Thailand [23]. A study reported by Santanoo et al [36] also showed that although CMR38-125-77 had moderate photosynthesis, it had high-water use efficiency and efficient protective mechanisms, including high non-photochemical quenching and leaf drooping. These were useful traits for growth performance and canopy development for this cassava genotype.…”
Section: Discussionmentioning
confidence: 84%
“…Satisfactory performances for CMR38-125-77 on chlorophyll fluorescence, storage root dry weight, growth rate, total dry weight, starch content and starch yield have been reported in the previous investigations conducted in different upper paddy fields in rotation with rice (off-season) [12,13,35], as well as experiments conducted in different growing seasons under full irrigation in Thailand [23]. A study reported by Santanoo et al [36] also showed that although CMR38-125-77 had moderate photosynthesis, it had high-water use efficiency and efficient protective mechanisms, including high non-photochemical quenching and leaf drooping. These were useful traits for growth performance and canopy development for this cassava genotype.…”
Section: Discussionmentioning
confidence: 84%
“…Relative humidity also affects the uptake of water and nutrients, as well as photosynthesis. The leaf photosynthetic rate of cassava varied among the genotypes from 25-31 µmol (CO 2 ) m −2 s −1 in higher RH, and 7-20 µmol (CO 2 ) m −2 s −1 in lower RH environments, in which the differences among the cassava genotypes were possibly due to the stomatal adjustment [34,35]. Accordingly, the production of cassava in more humid environments (at 70% RH) had more total biomass and storage root yield than in low RH at 30% [36].…”
Section: Discussionmentioning
confidence: 99%
“…The same leaves were then preadapted to a dark period for one hour by fixing special tags on each leaf blade before measurements were retaken. After one hour of dark adaptation, the sensor cup was fitted on the leaf for measurement of maximum quantum efficiency of photosystem II photochemistry (Fv/Fm) [12,14,[18][19][20][21]. Relative water content (RWC) for those the same leaves as Pn and chlorophyll fluorescence evaluations were recorded between 9.00-10.00 a.m., where 1 cm 2 in leaf area was collected using a leaf disc borer.…”
Section: Soil Moisture Content =mentioning
confidence: 99%